Monitoring urban beaches with qPCR vs. culture measures of fecal indicator bacteria: Implications for public notification - Samuel Dorevitch; Abhilasha Shrestha; Stephanie DeFlorio-Barker; Cathy Breitenbach; Ira Heimler (BMC, 2017)
Abstract Background The United States Environmental Protection Agency has established methods for testing beach water using the rapid quantitative polymerase chain reaction (qPCR) method, as well as "beach action values" so that the results of such testing can be used to make same-day beach management decisions. Despite its numerous advantages over culture-based monitoring approaches, qPCR monitoring has yet to become widely used in the US or elsewhere. Considering qPCR results obtained on a given day as the best available measure of that day's water quality, we evaluated the frequency of correct vs. incorrect beach management decisions that are driven by culture testing. Methods Beaches in Chicago, USA, were monitored using E. coli culture and enterococci qPCR methods over 894 beach-days in the summers of 2015 and 2016. Agreement in beach management using the two methods, after taking into account agreement due to chance, was summarized using Cohen's kappa statistic. Results No meaningful agreement (beyond that expected by chance) was observed between beach management actions driven by the two pieces of information available to beach managers on a given day: enterococci qPCR results ofsamples collected that morning and E. coli culture results of samples collected the previous day. The E. coli culture beach action value was exceeded 3.4 times more frequently than the enterococci qPCR beach action value (22.6 vs. 6.6% of beach-days). Conclusions The largest evaluation of qPCR-based beach monitoring to date provides little scientific rationale for continued E. coli culture testing of beach water in our setting. The observation that the E. coli culture beach action value was exceeded three times as frequently as the enterococci qPCR beach action value suggests that, although the beach action values for bacteria using different measurement methods are thought to provide comparable information about health risk, this does not appear to be the case in all settings.